Respuesta :

Answer:

13/115

Step-by-step explanation:

[tex]f(0)=\frac{2(0)-1}{3(0)+5}=-\frac{1}{5} \\ \\ f(6)=\frac{2(6)-1}{3(6)+5}=\frac{11}{23} \\ \\ \frac{f(6)-f(0)}{6-0} =\frac{\frac{11}{23}+\frac{1}{5}}{6}=\boxed{\frac{13}{115}}[/tex]

Sprnt

Answer:

13/115.

Step-by-step explanation:

Formula for the average rate of change of a function:

[tex]A(x)=\frac{f(b)-f(a)}{b-a}[/tex]

Say that b=6 and a=0.

Find the values that the function gives with these 2 values:

[tex]f(6)=\frac{2(6)-1}{3(6)+5}=\frac{11}{23} \\\\f(0)=\frac{2(0)-1}{3(0)+5}=\frac{-1}{5} \\\\[/tex]

Now we substitute these values in the formula:

[tex]A(x)=\frac{(\frac{11}{23} )-(\frac{-1}{5} )}{6-0}[/tex]

Let's solve the fraction substraction:

[tex]\frac{11}{23}- \frac{-1}{5}=\frac{11}{23}+ \frac{1}{5}=\frac{55}{115}+ \frac{23}{115}=\frac{78}{115}[/tex]

Substitute and solve the division:

[tex]A(x)=\frac{\frac{78}{115} }{6}= \frac{78}{115}*\frac{1}{6} =\frac{78}{690}=\frac{13}{115}[/tex]